2021
DOI: 10.3390/en14113314
|View full text |Cite
|
Sign up to set email alerts
|

Comfort of Domestic Water in Residential Buildings: Flow, Temperature and Energy in Draw-Off Points: Field Study in Two Danish Detached Houses

Abstract: There is very little knowledge on the occupant actual hot water comfort (temperature and flow), usage practice, and routines (temporal and spatial distribution of hot water usage in a household). This paper describes the results from the total and hot water measurements in two Danish detached houses. The results show that, at the draw-off points, the temperature of 55 °C is never asked by the occupants, not even in the kitchen sink. The domestic water temperature differentiates depending on the function of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It is possible to discuss the value of the hot water temperature that should be used in the calculations. The results of studies of two single-family houses in Denmark [62] showed that the temperature of the water used in the shower was 35.5 • C to 40.4 • C, and for hand washing 20.5 • C to 26.5 • C. Taking the bath as a representative device and assuming the hot water temperature of 40 • C seems to be justified in the context of the quoted research results.…”
Section: Hot Water Consumption-sander's Methodsmentioning
confidence: 92%
“…It is possible to discuss the value of the hot water temperature that should be used in the calculations. The results of studies of two single-family houses in Denmark [62] showed that the temperature of the water used in the shower was 35.5 • C to 40.4 • C, and for hand washing 20.5 • C to 26.5 • C. Taking the bath as a representative device and assuming the hot water temperature of 40 • C seems to be justified in the context of the quoted research results.…”
Section: Hot Water Consumption-sander's Methodsmentioning
confidence: 92%
“…For instantaneous water heating technologies, discomfort is assumed to be always zero. In this study a more restrictive approach than in [82] was used.…”
Section: Methodsmentioning
confidence: 99%
“…This may impair the stability and reliability of energy grids. The metered heat data reflect practices related to space heating, such as heating and comfort practices [19,20], as well as DHW usage, such as showering and personal hygiene [18], where the shower and kitchen taps are found to constitute around 90% of the total DHW usage [21]. Thus, the data result from a complex interaction between occupants, building physics, and heating systems, particularly the components responsible for the indoor temperature adjustment and the use of DHW (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the data result from a complex interaction between occupants, building physics, and heating systems, particularly the components responsible for the indoor temperature adjustment and the use of DHW (see Figure 1). One should note that the share of DHW and space heating in the total building heat demand varies significantly from buildings to buildings, depending on the occupants' habits and the energy performance of the building envelope [14,16,21].…”
Section: Introductionmentioning
confidence: 99%